Older persons’ emotional responses to the built environment: An analysis of walking experiences in central neighbourhoods of Santiago de Chile - Marie Geraldine Herrmann-Lunecke; Cristhian Figueroa-Martínez; Bárbara Olivares Espinoza (Transportation Research Interdisciplinary Perspectives)
Walking reports numerous benefits for older persons, yet there is significant evidence indicating that the features of the built environment of contemporary cities are compromising its practice. This article explores how the built environment affects older persons’ walking experiences, by analysing older persons’ self-reported emotional responses to the built environment. More in detail, this article examines the findings of a set of walking interviews in which forty older persons (between 60 and 79 years old) who resided in central areas of Santiago de Chile were invited to walk in their neighbourhoods and talk about the features of the built environment that affect the journeys they complete on foot and the emotions they elicit. The analysis shows that the built environment is an emotional issue for the participants, which has a significant impact on their well-being and everyday life. The older persons declared that while walking certain features of the built environment can elicit wellness (e.g., greenery) and unwellness (e.g., narrow sidewalks), stress (e.g., crossings), and resignation (e.g., motorized traffic), among other emotions. Finally, the article reflects upon how urban planning and design can make substantial contributions in improving the built environment to enhance older adults’ walking experiences.